Clinically Prepared Veterinary Students: Enhancing Veterinary Student Hands-on Experiences and Supporting Hospital Caseload Using Shelter Medicine Program - Shivley, Jacob M.; Brookshire, Wilson C.; Bushby, Philip A.; Woodruff, Kimberly A. (Frontiers in Veterinary Science, 2018)
Referral-level medicine is important in the veterinary curriculum, however veterinary students also need a solid base knowledge of clinically relevant, routine surgical and diagnostic skills to be clinically prepared after graduation. Exposure to a referral-only, or primarily referral caseload, does not always provide veterinary students with the routine hands-on experiences and competencies expected by the American Veterinary Medical Association Council on Education, the Royal College of Veterinary Surgeons, the Australian Veterinary Boards Council, or prospective employers. The aim of this descriptive study was to assess how a shelter medicine program can fill the companion animal caseload gap and create the necessary hands-on experiences considered essential in the veterinary curriculum. Pedagogical frameworks, course curriculum and design, student experiences, and student assessments were described for three core curricular areas (surgery, medical days, population medicine) of the Shelter Medicine Program at Mississippi State University. The shelter surgery experience provided a high-quality, high-volume spay/neuter environment where fourth-year students averaged 65 sterilization surgeries in two weeks and demonstrated a quantifiable decrease in surgical time. The shelter surgery experience added on average 9,000 small animal cases per year to the overall hospital caseload. Shelter medical days, where students provide veterinary care during on-site shelter visits, created opportunities for third-year students to directly interact with shelter animals by performing physical examinations and diagnostic testing, and to gain experience in developing treatment protocols and recommendations for commonly encountered problems. The shelter medical days experience averaged over 700 small animal cases per year and over 1500 diagnostic procedures. Finally, students participated in 15 onsite shelter consultations where they obtained a working knowledge of biosecurity at a population level, including how to minimize the risk of infectious diseases spreading to healthy populations. Despite several challenges, results from this curricular program assessment support the aim that animal shelters and humane organizations offer opportunities that can be mutually beneficial for both animal organizations and veterinary students. The primary care caseload for the teaching institution was positively impacted, and students were better prepared to meet potential employers' expectations and fulfill required core competencies in veterinary medical education.